(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to evaluate the financial performance of Libyan commercial banks, with a particular focus on the Bank of Commerce and Development during the period 2016–2023, using the PATROL model adopted by the Central Bank of Italy for bank evaluation. The model consists of five indicators: capital adequacy, profitability, credit quality, organization, and liquidity. The research problem was centered on answering the main question: Can the PATROL model be used to evaluate the financial performance of the Bank of Commerce and Development? The study employed the descriptive-analytical approach to analyze data extracted from the bank’s financial statements. The findings revealed several results, the most important of which are: the capital adequacy indicator showed that the bank maintained a ratio within the “excellent” category (1) throughout the study period according to the PATROL model. This indicates the strength and robustness of the bank’s capital and its ability to face risks, providing a high degree of safety for depositors, since capital is considered the primary protection and safeguard. The study further revealed that the overall average of the credit quality indicator according to the PATROL model was rated (2.6), due to the increase in provisions for doubtful debts. This reflects high credit risk and confirms that the lending policy of the Bank of Commerce and Development is not prudent, emphasizing the need to restructure its credit policies. The study recommended the necessity of activating surplus liquidity management policies in a way that achieves balance between meeting operational needs and investing resources in profitable opportunities. It also emphasized intensifying efforts to improve organizational efficiency through stricter control of expenses and enhancing income diversification, as the study showed that the overall average of the organizational indicator according to the PATROL model was (3).